STUDY ON ULTRAVIOLET RESISTANCE OF WOOD PLASTIC COMPOSITE PRODUCED FROM ACACIA MANGIUM BARK AND NANO TiO2 - Quoc An, Cao; Van Hai, Trieu (Journal of Forestry Science and Technology, 2016)
This study determined effect of nano TiO2 ratio on some properties of wood plastic composite (WPC), especially ultraviolet (UV) resistance of the material. Research results showed that, the TiO2 nanoparticles did not significantly affect bonding quality between wood flour and plastic, it means when adding nanoparticles into WPC, the strength of material was almost unchanged. However, the abrasion ability of the material was significantly affected. The results revealed that, when the nano TiO2 ratio increased, the mass loss of WPC due to abrasion reduced; therefore the abrasion resistance of WPC increased as added nano ratio increased, when the used nanoparticles ratio was 0.5%, the mass loss due to abrasion of WPC was 0.42 g/100r, but when the used nanoparticles ratio increased to 1.5%, the mass loss due to abrasion of WPC reduced to 0.31 g/100r. Moreover, adding TiO2 into the WPC production process from Acacia mangium bark could increase the color stability of the material under UV radiation. The results also presented that, with the samples did not contain nano TiO2, DE value was about 9 to 10, but with the samples containing TiO2, the DE values reduced from 3 to 5 (40-50% reduction).